Toán Lớp 8: 1. Thu gọn biểu thức a) (x-3) ² + 3x (x-5) b) (3x+2) ² – (x+3) (x-3) 2. Tìm x biết a) (x+4) ² – (x+2) (x-2)=5 b) (3x-1) ² _ (2x-3) (4x+

Question

Toán Lớp 8: 1. Thu gọn biểu thức
a) (x-3) ² + 3x (x-5)
b) (3x+2) ² – (x+3) (x-3)
2. Tìm x biết
a) (x+4) ² – (x+2) (x-2)=5
b) (3x-1) ² _ (2x-3) (4x+1)= 5+x ², hướng dẫn giải giúp em bài này ạ, em cảm ơn thầy cô và các bạn nhiều.

in progress 0
Hương 1 tháng 2022-12-21T12:43:27+00:00 2 Answers 0 views 0

TRẢ LỜI ( 2 )

  1. Bài 1 :
    $ a) ( x – 3 )^2 + 3x ( x – 5 ) $
    $ = x^2 – 6x +9 + 3x^2 – 15x $
    $ = 4x^2 – 21x + 9 $
    $ b) ( 3x + 2 )^2 – ( x + 3 ) ( x – 3 )  $
    $ = 9x^2 + 12x + 4 – x^2 + 9 $
    $ = 8x^2 + 12x + 13 $
    Bài 2 :
    $ a) ( x + 4 )^2 – ( x+2 ) ( x- 2 ) = 5 $
    ⇒ $ x^2 + 8x +16 -x^2 + 4 = 5 $
    ⇒ $ 8x + 20 = 5 $
    ⇒ $ 8x = – 15 $
    ⇒ $ x = – \dfrac{15}{8} $
    Vậy $ x = – \dfrac{15}{8} $
    $ b) ( 3x – 1 )^2 – ( 2x – 3 ) ( 4x + 1 )= 5 + x^2$
    ⇒ $ 9x^2 – 6x + 1 – (8x^2 – 12x +2x – 3 ) = 5 + x^2$
    ⇒ $ 9x^2 – 6x + 1 – 8x^2 + 12x – 2x + 3 – 5 – x^2 =0 $
    ⇒ $ 4x – 1 = 0 $
    ⇒ $ 4x = 1 $
    ⇒ $ x = \dfrac{1}{4} $
    Vậy $ x = \dfrac{1}{4} $
     

  2. Bài 1:
    a) (x-3)^2+3x(x-5)
    =x^2-6x+9+3x^2-15x
    =4x^2-21x+9
    b) (3x+2)^2-(x+3)(x-3)
    =9x^2+12x+4-x^2+9
    =8x^2+12x+13
    Bài 2:
    a) (x+4)^2-(x+2)(x-2)=5
    ⇔x^2+8x+16-x^2+4=5
    ⇔8x=5-4-16
    ⇔8x=-15
    ⇔x=-(15)/8
    Vậy x=-(15)/8
    b) (3x-1)^2-(2x-3)(4x+1)=5+x^2
    ⇔9x^2-6x+1-8x^2-2x+12x+3-x^2-5=0
    ⇔4x-1=0
    ⇔4x=1
    ⇔x=1/4
    Vậy x=1/4
     

Leave an answer

Browse

12:2+4x4-12:2-5x3 = ? ( )